Extracting specimen label data rapidly with a smartphone—a great help for simple digitization in taxonomy and collection management - Dirk Ahrens; Alexander Haas; Thaynara L. Pacheco; Peter Grobe (ZooKeys)
We provide short tutorials in how to read out specimen label data from type- as well as handwritten labels in a rapid and easy way with a mobile phone. We apply them in general, but test them in particular for insect specimen labels, which are generally quite small. We provide alterative procedure instructions for Android and Apple based environments, as well as protocols for single and bulk scans. We expect that this way of data capture will be of great help for a simple digitization in taxonomy and collection management, independent from large industrial digitization pipelines. By omitting the step of taking/maintaining images of the labels, this approach is more rapid, cheaper, and environmentally more sustainable because no storage with carbon footprint is required for label images. We see the biggest advantage of this protocol in the use of readily available commercial devices, which are easy to handle, as they are used on a daily basis and can be replaced at relatively low cost when they come into (informatic) age, which is also a matter of cyber security.